Pengaruh Likuiditas dan Profitabilitas Perbankan Syariah dengan Moderasi Efisiensi Operasional - Rizqa Ratna Febrista; Maria Rio Rita (Fakultas Ekonomi Dan Bisnis Islam IAIN Metro, 2020)
Sharia Commercial Banks will have high asset growth rates if they are balanced with a healthy bank performance. The distribution of financing illustrates the ability of bank liquidity that results in increased profitability. It turns out there are other factors that are suspected to affect the relationship between liquidity and profitability. This study is to examine the moderating effect of operational efficiency (BOPO) on the causal relationship between liquidity and profitability in Islamic banking. The results showed that banking efficiency was able to moderate the effect of liquidity on profitability. Banking efficiency is proven to strengthen the effect of liquidity on profitability in Islamic banking.